Loose and tower-type canopy structure can improve cotton yield in the Yellow River basin of China by increasing light interception. Issue 6 (12th May 2023) - An, Jie; Zhang, Zhenggui; Li, Xiaofei; Xing, Fangfang; Lei, Yaping; Yang, Beifang; Wang, Zhanbiao; Han, Yingchun; Chen, Huanxuan; Wang, Guoping; Feng, Lu; Du, Wenli; et al.
ABSTRACT: Determining the optimal plant architecture and canopy structure are important objectives in research on the breeding and cultivation of high-yielding crops. To address this challenge, a field experiment was conducted in Anyang, Henan, China, to assess cotton light interception, boll spatial distribution, leaf area index (LAI), plant height and biomass, lint yield and yield component during 2018–2019. Treatments including 10 cotton cultivars with belong to tower-shaped and tube-type canopy structure. Compared with compact cotton varieties, the loose and tower-shaped cotton varieties intercepted more light (average 28.6%) and had a higher LAI (average 34.2%), resulting in a higher cotton yield (average 14.8%). In addition, polynomial correlation showed that the maximum light interception rate occurred at the flowering and boll-forming stage, when the annual mean plant height (94.6 cm), LAI (3.58) and biomass (15, 006 kg ha −1 ) all reached their peak. Moreover, yield was extremely significantly positively correlated with intercepted photosynthetically active radiation (IPAR) (R = 0.7) and positively correlated with light use efficiency (LUE) (R = 0.36). Overall, the results suggest that cotton cultivars with loose and tower-type canopy structures intercept more light and should be planted to increase cotton yield and LUE in the Yellow River basin of China and areas with similar conditions.